Mechanotransduction as an Adaptation to Gravity - Najrana, Tanbir; Sanchez-Esteban, Juan (Frontiers in Pediatrics, 2016)
Gravity has played a major role in the evolution of terrestrial life. A central event in evolution has been the development of mechanisms to sense and transduce gravitational force into biological signals. The objective of this manuscript is to review how living organisms on Earth use mechanotransduction as an adaptation to gravity. Certain cells have evolved specialized structures, such as otoliths in hair cells of the inner ear and statoliths in plants, to respond directly to the force of gravity. By conducting studies in the reduced gravity of spaceflight [microgravity] or simulating microgravity in the laboratory, we have gained insights into how the physical force of gravity might have shaped life on Earth. We review how microgravity affects prokaryotic and eukaryotic cells at the cellular and molecular levels. Genomic studies in yeast have identified changes in genes involved in budding, cell polarity and cell separation regulated by Ras, PI3K and TOR signaling pathways. Moreover, transcriptomic analysis of late pregnant rats have revealed that microgravity affects genes that regulate circadian clocks, activate mechanotransduction pathways and induce changes in immune response, metabolism and cells proliferation. Importantly, these studies identified genes that modify chromatin structure and methylation, suggesting that long term adaptation to gravity may be mediated by epigenetic modifications. Given that gravity represents a modification in mechanical stresses encounter by the cells, the tensegrity model of cytoskeletal architecture provides an excellent paradigm to explain how changes in the balance of forces, that are transmitted across transmembrane receptors and cytoskeleton, can influence intracellular signaling pathways and gene expression